Long-term Evaluation of Fistulotomy and Immediate Sphincteroplasty as a Treatment for Complex Anal Fistula. Issue 11 (November 2021) - Aguilar-Martínez, María del Mar; Sánchez-Guillén, Luis; Barber-Valles, Xavier; Alcaide-Quirós, María José; Bosch-Ramírez, Marina; López-Delgado, Alberto; Tozer, Phil; Arroyo, Antonio
Abstract : BACKGROUND: Fistulotomy with immediate sphincteroplasty is a technique that can heal fistulas and decrease fecal incontinence more effectively than fistulotomy alone, in selected patients. OBJECTIVE: We aimed to perform a long-term evaluation of fecal incontinence after fistulotomy and immediate sphincteroplasty in patients with complex anal fistula. DESIGN: This prospective study included patients undergoing fistulotomy and immediate sphincteroplasty for complex anal fistula from January 2000 to December 2010. SETTINGS: The study was conducted by 2 colorectal surgeons in the coloproctology unit of the General Hospital of Elche. PATIENTS: We included patients aged ≥18 years with complex anal fistulas of cryptoglandular origin. MAIN OUTCOME MEASURES: Main outcomes were recurrence and continence after fistulotomy and immediate sphincteroplasty, according to fistula tract height and preoperative continence status. RESULTS: A total of 107 patients were included; 68.2% were men, with a mean age of 48 years and mean fistula duration of 12.8 months. The range and median follow-up period were 84 to 204 and 96 months. Thirty-seven fistulas were not primary. The overall healing rate was 84.1%. Primary fistulas healed by the end of follow-up in 58 (82.9%) of 70 patients; recurrent fistulas healed in 32 (86.5%) of 37; high tracts healed in 31 (83.8%) of 37, and nonhigh fistulas healed in 59 (84.3%) of 70. Male sex (OR = 0.66 (95% CI, 0.20–2.13); p > 0.05) and recurrent fistulas (OR = 0.43 (95% CI, 0.11–1.68); p > 0.05) could have a protective effect against postoperative fecal incontinence; however, more studies with larger sample sizes are necessary to confirm this result, whereas high fistulas showed a 4-fold increased risk of incontinence (range, 1.22–13.06; p < 0.01). One in 5 high-tracts patients experienced continence deterioration. LIMITATIONS: This was a prospective study, and randomized clinical trials with more patients and longer follow-up are needed to compare fistulotomy and immediate sphincteroplasty with other sphincter-preserving techniques. CONCLUSIONS: Fistulotomy and immediate sphincteroplasty are good options for treating complex anal fistulas, especially for recurrent fistulas, men, and patients with nonhigh tracts, with acceptable recurrence and incontinence rates. See Video Abstract at http://links.lww.com/DCR/B498 . EVALUACIÓN A LARGO PLAZO DE LA FISTULOTOMÍA Y LA ESFINTEROPLASTIA INMEDIATA COMO TRATAMIENTO PARA LA FÍSTULA ANAL COMPLEJA: ANTECEDENTES: La fistulotomía y la esfinteroplastia inmediata es una técnica que puede curar las fístulas y disminuir la incontinencia fecal de manera más efectiva que la fistulotomía sola, en pacientes seleccionados. OBJETIVO: Nuestro objetivo fue realizar una evaluación a largo plazo de la incontinencia fecal después de la fistulotomía y la esfinteroplastia inmediata en pacientes con fístula anal compleja. DISEÑO: Este estudio prospectivo incluyó pacientes sometidos a fistulotomía y esfinteroplastia inmediata por fístula anal compleja, desde enero de 2000 hasta diciembre de 2010. ENTORNO CLINICO: El estudio fue realizado por dos cirujanos colorrectales de la Unidad de Coloproctología del Hospital General de Elche. PACIENTES: Se incluyeron pacientes ≥ 18 años con fístulas anales complejas de origen criptoglandular. PRINCIPALES MEDIDAS DE VALORACION: Los principales resultados fueron la recurrencia y la continencia después de la fistulotomía y la esfinteroplastia inmediata, de acuerdo con la altura del trayecto de la fístula y el estado de continencia preoperatoria. RESULTADOS: Se incluyeron un total de 107 pacientes; El 68, 2% eran varones, con una edad media de 48 años y una duración media de la fístula de 12, 8 meses. El rango y la mediana del período de seguimiento fue de 84-204 y 96 meses, respectivamente. Treinta y siete fístulas no fueron primarias. La tasa de curación general fue del 84, 1%. Las fístulas primarias cicatrizaron al final del seguimiento en 58/70 (82, 9%) pacientes; las fístulas recurrentes cicatrizaron en 32/37 (86, 5%); los tractos altos cicatrizaron en 31/37 (83, 8%) y las fístulas no altas cicatrizaron en 59/70 (84, 3%). El sexo masculino (razón de posibilidades: 0, 66 [0, 20-2, 13], p > 0, 05) y las fístulas recurrentes (razón de posibilidades: 0, 43 [0, 11-1, 68], p > 0, 05) podrían tener un efecto protector contra la incontinencia fecal postoperatoria, sin embargo, más estudios con una muestra más grande son necesarios para confirmar este resultado. Fistulas altas mostraron un riesgo cuatro veces mayor de incontinencia ([1.22-13.06], p < 0.01). Uno de cada cinco pacientes con tractos altos experimentó un deterioro de la continencia. LIMITACIONES: Este fue un estudio prospectivo y se necesitan ensayos clínicos aleatorios con más pacientes y un seguimiento más prolongado para comparar la fistulotomía y la esfinteroplastia inmediata con otras técnicas de preservación del esfínter. CONCLUSIÓN: La fistulotomía y la esfinteroplastia inmediata son buenas opciones para el tratamiento de fístulas anales complejas, especialmente para fístulas recurrentes, varones y pacientes con tractos no altos, con tasas aceptables de recurrencia e incontinencia. Consulte Video Resumen en http://links.lww.com/DCR/B498 .